2001
DOI: 10.2188/jea.11.238
|View full text |Cite
|
Sign up to set email alerts
|

Natural Killer Activity and Its Changes among Participants in a Smoking Cessation Intervention Program. A Prospective Pilot Study of 6 Months' Duration.

Abstract: We examined the effect of smoking cessation on natural killer (NK) activity of peripheral blood lymphocytes in terms of a prospective study of 27 Japanese subjects who participated in a smoking cessation intervention program. This program was delivered by means of group-counseling offering 7 sessions of about 2 hours over 6 months to help smokers to discontinue the habit. Thirteen subjects ceased smoking (quitters), while 14 continued to smoke (cigarette smokers). NK activity before the intervention was correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2005
2005
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
0
5
0
2
Order By: Relevance
“…Because NK cells can control and regulate viral infections via killing of infected respiratory epithelial cells, altered NK cell functions in smokers could contribute to enhanced influenza infections. Although smoking has been shown to suppress peripheral NK cell activity ex vivo [22-26], the effects of smoking on respiratory NK cell functions are unknown [24]. …”
Section: Introductionmentioning
confidence: 99%
“…Because NK cells can control and regulate viral infections via killing of infected respiratory epithelial cells, altered NK cell functions in smokers could contribute to enhanced influenza infections. Although smoking has been shown to suppress peripheral NK cell activity ex vivo [22-26], the effects of smoking on respiratory NK cell functions are unknown [24]. …”
Section: Introductionmentioning
confidence: 99%
“…This is because chemical carcinogens in the BQ, tobacco and alcohol may attack the protein, lipid and DNA of mucosal cells, leading to gene mutation, chromosomal aberrations and clinical oral cancer 30,34 . Most damaged DNA can be repaired and the transformed cells can be destroyed by the immune defense system, but some transformed cells may overcome the immune surveillance resulting in cancer development and progression 3,15,22,23,44 .…”
mentioning
confidence: 99%
“…A study of young cigarette smokers (age 21–35) who quit smoking showed that NKCA recovery was detectable 31 days after cessation (Meliska et al). In contrast, a prospective study of 6‐month smoking cessation on immunity found a small NKCA increase after cessation among quitters younger than age 65, but not among quitters who were at least 65 years old (Ioka et al, 2001). Immune function recovery through smoking cessation may be influenced by cumulative pack years of smoking before cessation and levels of SHS exposure after cessation (Nakata et al, 2004, 2007), as well as changes in other behavioral factors.…”
Section: Smoking Cessation and Immunitymentioning
confidence: 97%